The Contribution of Self-Regulated Learning and Peer Social Support to Academic Procrastination in Completing Thesis - Rohani; Subhan, Mhd; Habibah, Suci; Nurhafiza, Nurhafiza; Ananda, Amelia (Indonesian Journal of Counseling and Development, 2025)
This study aims to examine the contribution of self-regulated learning and peer social support to academic procrastination among university students in completing their thesis. Meanwhile, peer social support provides emotional and motivational assistance that can help students overcome academic stress and maintain their commitment to completing tasks. Using a quantitative correlational design, the research population is 2353 students of the Faculty of Tarbiyah and Teacher Training which was found to be a sample of 100 students who used the Taro Yamane formula. The analysis of this study uses description, simple and multiple linear regression. The analysis of research data was conducted using the Statistical Product and Service Solution (SPSS) 28 For Windows application. The results showed that both self-regulated learning and peer social support significantly contribute to reducing academic procrastination, with self-regulated learning having a stronger influence. Furthermore, the combination of these two factors explained a substantial portion of the variance in procrastination behaviour. The findings suggest that interventions aimed at improving students’ self-regulation skills and fostering supportive peer networks can effectively decrease procrastination and enhance thesis completion rates. This study provides valuable insights for educators and academic counsellors in designing comprehensive support programs to assist students in overcoming procrastination challenges